Dormancy breaking of 'Kampai' peach trees with alternative products in subtropical regions. (10th November 2021) - Viol, R. E.; Peche, P. M.; Farias, D. H.; Vilas Boas, L. V.; Curi, P. N.; Schiassi, M. C. E. V.; Pio, R.
Abstract: Peach trees initiate flowering and then dense budding when the temperatures in winter are steadily low. When temperatures during the winter are high or when the chilling accumulation needs of the cultivar are not met, it is necessary to apply chemicals that stimulate flowering and budding in a uniform manner. This study aimed to evaluate alternative products for breaking the dormancy of 'Kampai' peach trees in a subtropical region. The experiment was conducted with 'Kampai' peach trees in the 2018, 2019 and 2020 production with the following treatments: (1) negative control composed only of water (control); (2) positive control composed of hydrogen cyanamide at a dose of 1.5% (commercial product Dormex ® ) plus 4.5% mineral oil; (3) Erger G ® organomineral fertilizer supplemented with calcium nitrate at a dose of 3%; (4) potassium nitrate at a dose of 5%; and (5) copper sulphate at a dose of 0.3%. We evaluated affected budding capacity, flowering, the production cycle, peach production, the quality of peach trees and the enzymatic activities of catalase and guaiacol peroxidase. Hydrogen cyanamide and the organomineral fertilizer Erger G ® promoted earlier flowering and an earlier production cycle. On the other hand, hydrogen cyanamide and copper sulphate stimulated flower opening and peach production. The chemicals used decreased catalase activity (24 h after application) and increased guaiacol peroxidase activity (6 h after application). The application of copper sulphate may be an option to break the dormancy of peach trees in the subtropics.